Catalytic Asymmetric Total Synthesis of (+)-Yohimbine - Mergott, Dustin J; Zuend, Stephan J; Jacobsen, Eric N (Organic letters, 2008)
The total synthesis of (+)-yohimbine was achieved in 11 steps and 14% overall yield. The absolute configuration was established through a highly enantioselective thiourea-catalyzed acyl-Pictet−Spengler reaction, and the remaining 4 stereocenters were set simultaneously in a substrate-controlled intramolecular Diels−Alder reaction.